Analisis tingkat kepuasan pasien atas kualitas pelayanan Poli Gigi Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Pekanbaru - Yulia, Mitra; Restuti, Sri; Noviasari, Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at Poli Gigi of RSUD Arifin Ahmad Pekanbaru the purposes of the research were to find out the patients satisfaction toward service quality that covered tangibles, reability, responsiveness, assurance, and emphaty. There were 100 respondents. The samples were taken by accidental sampling. The importance performance analysis (IPA) was used to analyze the data by using kartesius diagram. The diagram kartesius was used to identify service and the quality degree of companies services. The result of the research showed that the dimension satisfied the Poli Gigi patients of RSUD Arifin Ahmad Pekanbaru was tangiable dimension. It was 76% for tangiable dimension and assurance dimension was 71%. Meanwhile, the reliability and responsive dimension gave enough satisfaction 68%, and empathy dimension was 69%. In order to get more satisfaction and improve the Poli Gigi image, they were suggested to increase the quality services.Keywords: Satisfaction of Patients, Tangibles, Reliability, Responsiveness, Assurance and Emphaty.